Respuestas

¡La mejor respuesta!
2012-06-26T23:25:27+02:00

comensemos:

 

-3x  +  5y  = 6   -----> primera

 4        3

 

x  -  2y  = 8  --------> segunda

9      3

 

entonces:

 

primera:

 

-3x  +  5y  = 6 

 4        3

 

-3x*3 + 5y*4 =6

      4*3

 

-9x+20y = 6

    12

 

-9x+20y = 6*12

 

-9x+20y = 72

 

segunda:

 

x  -  2y  = 8  

9      3

 

x*3-2y*9 = 8

   9*3

 

3x-18y = 8

   27

 

3x-18y = 8*27

 

3x-18y = 216

 

entonces:

 

-9x+20y = 72  -------> primera

 

3x-18y = 216  -------> segunda

 

multiplicamos:

 

-9x +20y=72

3*(3x-18y)=3*(216)

 

-9x+20y=72   (+)

9x-54y=648

20y-54y=72+648

 

-34y=720

 

y=720

   -34

 

y= - 360

        17

 

remplazando para hallar x:

 

-9x +20y=72

 

-9x + 20*(-360) = 72

                 17

 

-9x - 7200 = 72 

         17

 

-9x = 72 + 7200

                 17

 

-9x = 8424

          17

 

x = - 936

        17

 

un gusto....=D  (esta paso a paso ...=D)